Farrow-to-Finish Swine Cost-Return Projection - Dhuyvetter, Kevin C.; Jones, Rodney D.; Tokach, Mike D. (My University, 1997)
This publication examines the cost and returns for farrow to finish swine production in Kansas.
MF292_1997_10
Keywords: MF292; Livestock; Economics; MF